EXPERIMENTAL SIMULATIONS OF GAS-DRIVEN ERUPTIONS: KINETICS OF BUBBLE GROWTH AND EFFECT OF GEOMETRY - Zhang Y. (My University, 1998)
Simulated gas-driven eruptions using CO2-water-polymer systems are reported. Eruptions are initiated by rapidly decompressing CO2-saturated water containing up to 1.0 wt.% CO2. Both cylindrical test cells and a flask test cell were used to examine the effect of magma chamber/conduit geometry on eruption dynamics. Bubble-growth kinetics are examined quantitatively in experiments using cylindrical test cells. Uninhibited bubble growth can be roughly expressed as dr/dt≈λD(β-1)/(γt1/3) for a CO2-water-polymer system at 0-22 °C and with viscosities up to 5 Pa·s, where r is the radius of bubbles, λ and D are the Ostwald solubility coefficient and diffusivity of the gas in the liquid, β is the degree of saturation (decompression ratio), and γ characterizes how the boundary layer thickness increases with time and is roughly 1.0×10-5 m/s1/3 in this system. Unlike the radius of cylindrical test cells, which does not affect the eruption threshold and dynamics, the shape of the test cells (flask vs cylindrical) affects the dynamics but not the threshold of eruptions. For cylindrical test cells, the front motion is characterized by constant acceleration with both Δh (the height increase) and ΔV (the volume increase) being proportional to t2; for the flask test cell, however, neither Δh nor ΔV is proportional to t2 as the conduit radius varies. Test-cell geometry also affects foam stability. In the flask test cell, as it moves from the wider base chamber into the narrower conduit, the bubbly flow becomes fragmented, affecting the eruption dynamics. The fragmentation may be caused by a sudden increase in acceleration induced by conduit-shape change, or by the presence of obstacles to the bubbly flow. This result may help explain the range in vesicularities of pumice and reticulite.
Keywords: GAS-DRIVEN ERUPTIONS; EXPLOSIVE VOLCANISM; LIMNIC ERUPTIONS; PUMICE; EXPERIMENTAL VOLCANOLOGY; BUBBLE GROWTH; VESICULARITY